Spatio‐Temporal Variation in Perkinsus olseni Infection Intensity in Manila Clam Ruditapes philippinarum in Anmyeondo and Cheonsu Bay Tidal Flats on the West Coast of Korea - Thatchaneshkanth, S.; Young‐Ghan, C.; Hye‐Mi, L.; Jeong‐Hwa, K.; Jong‐Seop, S.; Mun‐Gyeong, K.; Gwang‐Il Jang, J.; · Kwang‐Sik, C. (Korea Institute of Ocean Science & Technology and The Korean Society of Oceanography, 2024)
The alveolate protist Perkinsus olseni infections impose considerable stresses on the host Manila clam Ruditapes philippinarum, often reducing their tissue weight due to the drain on energy resources. However, the relationship between condition factors and P. olseni infection exhibits inconsistency in different scenarios, as it is influenced by various factors such as environmental conditions, food availability, and reproductive conditions. To gain deeper insights, we surveyed Manila clams occurring on tidal flats in Anmyeondo Island, Cheonsu Bay to assess P. olseni intensity and its effects on the fitness of Manila clams. The Ray’s fluid thioglycollate medium assay revealed that P. olseni infection in clams from inner Cheonsu Bay had considerably greater P. olseni intensities in May and September 2021 than those from outer Cheonsu Bay and reference sites (P < 0.05). Despite the high level of P. olseni infection, condition index (CI), a ratio of the flesh weight to the shell weight, in clams from inner Cheonsu Bay was also significantly higher than in clams from outer Cheonsu Bay and reference sites (P < 0.05). A noteworthy finding of this study was the positive association between P. olseni infection intensity and CI in clams, which suggests that despite the high parasite load, clams were able to maintain a higher CI, possibly due to the abundance of nutrients and organic matter present in the inner bay. The P. olseni infection intensities measured in September were significantly higher at most of the sampling sites in the inner and outer bay, which could be associated with the poor health condition of clams during a post-spawning period. These results highlight the complexity of bivalves’ ecological relationships in Cheonsu Bay and offer new insights into their adaptability accompanied by other factors to parasite stressors.
Keywords: Perkinsus; Condition index; Ruditapes philippinarum; Infection intensity; Manila clam